Enhancing Photoluminescence of Nonconventional Luminescent Polymers by Increasing Chain Flexibility. Issue 19 (9th September 2019) - Shang, Cong; Zhao, Yaxin; Wei, Nan; Zhuo, Hongmei; Shao, Yumei; Wang, Huiliang
Abstract: Many nonconventional luminescent polymers are found to exhibit intrinsic photoluminescence and "aggregation‐induced emission" (AIE) behavior. Strong physical interactions among polymer chains and/or a rigid molecular conformation of polymer chains are thought to be beneficial to boost stronger emissions. The purpose of this work is to prove that increasing chain flexibility is, at least in some cases, beneficial to enhance the photoluminescence of nonconventional luminescent polymers. Poly(itaconic anhydride) (PITA) and poly[(1‐octene)‐ co ‐(itaconic anhydride)] (POITA) synthesized in this work are highly emissive in concentrated solutions and in solid state, exhibiting typical AIE characteristics, and very interestingly, the copolymer POITA exhibits stronger and red‐shifted emissions than the homopolymer PITA in both solutions and in the solid state. These results are explained by the increase of chain flexibility, which makes the nonconventional chromophores adopt proper conformations for strong intra‐ and/or interchain n‐π* and/or π–π* interactions. This study sheds some light on designing nonconventional luminescent materials with high emission efficiency and long wavelength emission. Abstract : By synthesizing and studying the photoluminescence of poly(itaconic anhydride) and poly[(1‐octene)‐ co ‐(itaconic anhydride)], it is proved that increasing chain flexibility is, at least in some cases, beneficial to enhance the photoluminescence of nonconventional luminescent polymers.